2015
DOI: 10.1037/a0039469
|View full text |Cite
|
Sign up to set email alerts
|

Modern attitudes toward older adults in the aging world: A cross-cultural meta-analysis.

Abstract: Prevailing beliefs suggest that Eastern cultures hold older adults in higher esteem than Western cultures do, due to stronger collectivist traditions of filial piety. However, in modern, industrialized societies, the strain presented by dramatic rises in population aging potentially threatens traditional cultural expectations. Addressing these competing hypotheses, a literature search located 37 eligible papers, comprising samples from 23 countries and 21,093 total participants, directly comparing Easterners a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
363
3
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 435 publications
(400 citation statements)
references
References 156 publications
(217 reference statements)
28
363
3
6
Order By: Relevance
“…These findings were supported by statistically significant results in regard to correlational analysis of the relevant variables (e.g., age and fear of getting old) and multiple analysis of variance interpretations. These findings have been noted in other studies looking at prejudice and stereotypes of the elderly and some common themes do seem to emerge, such as the elderly often being perceived as being frail, senile, incompetent, unproductive, and burdens on society [4] [9] [18]. It would appear that we also live in society that values youth over old age.…”
Section: Discussionmentioning
confidence: 73%
“…These findings were supported by statistically significant results in regard to correlational analysis of the relevant variables (e.g., age and fear of getting old) and multiple analysis of variance interpretations. These findings have been noted in other studies looking at prejudice and stereotypes of the elderly and some common themes do seem to emerge, such as the elderly often being perceived as being frail, senile, incompetent, unproductive, and burdens on society [4] [9] [18]. It would appear that we also live in society that values youth over old age.…”
Section: Discussionmentioning
confidence: 73%
“…Negative stereotypes about ageing are common [31]. Understanding the extent to which such internalised stereotypes affect health outcomes in older people has particular relevance in our rapidly ageing populations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall results were surprisingly, and significantly, in the opposite direction from lay beliefs: Easterners emerged as more negative overall toward older adults (overall standardized mean difference = -0.31; North & Fiske, 2015), and the majority of individual studies found this same pattern. However, these omnibus results were qualified by intraregional moderator analyses: First, East Asian regions appeared marginally more negative toward older generations than were South Asian regions; likewise, Western Europe emerged as more negative than Western Anglophone countries (i.e., U.S.A., U.K., Canada, Australia, New Zealand).…”
Section: International Manifestationsmentioning
confidence: 51%
“…A multiplemoderator meta-regression incorporating these variables found that, controlling for GDP (which was not a significant predictor of older-adult attitudes), population aging speed and cultural collectivism both predicted negativity toward older adults. This suggested that, controlling for level of recent industrialization, countries with more rapid population aging strain are coming to devalue their elders-especially in countries with high traditions of collectivism, which may backfire with a growing, potentially burdensome older population (North & Fiske, 2015).…”
Section: International Manifestationsmentioning
confidence: 97%
See 1 more Smart Citation